The Zombie argument against Materialism: the problem of construal and defense - Sepety, Dmytro (Actual Problems of Mind, 2017)
The article expounds one of the most influential arguments against materialism in the modern philosophy of mind, the zombie argument. It points out a grave deficiency in David Chalmers’ construal of the argument as involving the entailment from conceivability to logical possibility. Instead, an alternative construal is proposed and applied to defend the zombie argument against the charge of begging the question.